1998
DOI: 10.2500/108854198778557773
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sex Hormones on Eosinophilic Inflammation in Nasal Mucosa

Abstract: We examined the effects of sex hormones on the functions of eosinophils. Treatment of eosinophils with beta-estradiol significantly enhanced the eosinophil adhesion to human mucosal microvascular endothelial cells (HMMEC), and eosinophils stimulated by a combination of beta-estradiol and progesterone showed significant induced degranulation. On the other hand, testosterone significantly reduced the eosinophil adhesion to HMMEC and eosinophil viability. The experiments from the series of studies might provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 0 publications
1
79
0
2
Order By: Relevance
“…Few studies have evaluated the relationship between eosinophils and sex hormones. It seems that b-oestradiol significantly enhances eosinophil adhesion to human mucosal microvascular endothelial cells and their degranulation [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have evaluated the relationship between eosinophils and sex hormones. It seems that b-oestradiol significantly enhances eosinophil adhesion to human mucosal microvascular endothelial cells and their degranulation [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…(132). Similarly, a combination of estrogen and progesterone was able to significantly enhance human eosinophil degranulation (56). Other studies have found that estrogen treatment of eosinophils was capable of enhancing their adhesion to human mucosal microvascular endothelial cells, whereas testosterone reduced this effect (56).…”
Section: Eosinophilsmentioning
confidence: 99%
“…Therefore, a modulation of the allergic immune response by hormones as well as socio-cultural factors may contribute to gender differences encountered [8,21,34] .…”
mentioning
confidence: 99%
“…Additionally, female hormones increase the expression of histamine receptors on inflammatory cells and may promote eosinophilic inflammation [34] .…”
mentioning
confidence: 99%